Factors involved in the remission of oral lichen planus treated with topical corticosteroids - Poosit Wongpakorn; Soranun Chantarangsu; Chanwit Prapinjumrune (Nature Publishing Group, 2024)
Abstract Aim To determine the factors that affected the complete clinical remission of oral lichen planus (OLP) treated with topical corticosteroids. Material and methods We retrospectively evaluated the charts of patients diagnosed as OLP. Age, sex, current medical conditions, medications, type of OLP, Thongprasom score, pain level assessed by a numeric rating scale (NRS), Candida infection, topical steroid treatment preparation, duration of treatment until the first complete clinical remission, and follow-up duration were assessed as variables. Results In total 100 patients, after complete remission, 22 patients reported a relapse within 1.5-45 months, with a mean of 15.6 ± 13.2 months. Age, duration, gingiva and vestibule area, hypertension, dyslipidemia, Thongprasom score, preparation and topical corticosteroid potency were factors affecting the remission. Multivariate logistic regression analysis revealed that the patients' age and duration of treatment were significant factors after adjusted for age, sex, and independent factors with a P-value < 0.1 in the univariate analysis. The likelihood of having incomplete remission of the OLP lesion increased by 7.9% for every year increase in age and increased by 2.3% for every month of treatment. Conclusions There are many different factors between the complete remission and incomplete remission groups. However, age and duration of treatment were significant factors affecting the remission of OLP.